Evaluation of accepted and rejected submissions in the Journal of Applied Behavior Analysis: Gender and experience. Issue 3 (19th March 2021) - Kranak, Michael P.; Rooker, Griffin W.; Carr, Codey J.; Bradtke, Peter; Falligant, John Michael; Hausman, Nicole L.
Abstract : Researchers have examined factors of authors such as sex of author, gender identity, and seniority within the field of behavior analysis to determine if any biases towards a certain group existed. Most recently, Kranak et al. (2020) found that women and new authors are well‐represented in the Journal of Applied Behavior Analysis ( JABA ). However, that analysis included only published manuscripts. Thus, the degree to which these subpopulations are proportionally represented is unknown, because that analysis was unable to determine how often these subpopulations are submitting manuscripts. Therefore, the purpose of the current investigation was to extend Kranak et al. and analyze all accepted and rejected manuscripts submitted to JABA from 2015 – 2019. Results indicated that women and men had nearly identical acceptance rates during this time period, whereas veteran authors' acceptance rate was nearly 2.5 times greater than that of new authors. Implications for publishing, reviewing, and research mentorship practices are discussed.